Understanding Generation Z’s Preference for Cash on Delivery in Garut Regency - Gumilar, Irfan Rizki; Saepuloh, Asep; Syakinah, Fitri (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
This study examines the factors influencing Generation Z consumers' preferences for Cash on Delivery (COD) and their intention to continue using this payment method in Garut Regency, Indonesia. Despite the proliferation of electronic payment options, COD remains the predominant choice in e-commerce transactions. The research employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to investigate the impact of three key factors on the intention to continue using COD: risk perception, trust, and ease of use. The findings reveal that ease of use and risk perception significantly influence the intention to continue using COD, while trust does not demonstrate a significant effect. These results highlight the critical role of user-friendly payment systems and perceived risk in shaping the payment preferences of Generation Z consumers. The study contributes to the understanding of consumer behavior in emerging e-commerce markets and provides insights for businesses and policymakers seeking to optimize payment systems for younger demographics.